The Classroom Teacher's Guide to Music Education. - Burnsed, C. Vernon (Charles C Thomas Publisher, LTD, 1998)
This book is about music education in the elementary school. Its major purpose is to develop an understanding of why music education is important, how music education works, and how music can be a powerful force for the classroom teacher. It has realistic expectations for the classroom teacher. Music theory and performance skill are kept to a minimum; they are not a prerequisite for understanding the content of the book. A major emphasis of the text is that classroom teachers can utilize music to enhance the overall learning environment of their classrooms. Suggestions, class descriptions, and.